HD 222925: A New Opportunity to Explore the Astrophysical and Nuclear Conditions of r-process Sites - Erika M. Holmbeck; Rebecca Surman; Ian U. Roederer; G. C. McLaughlin; Anna Frebel (The Astrophysical Journal, 2023)
With the most trans-iron elements detected of any star outside the solar system, HD 222925 represents the most complete chemical inventory among metal-poor stars enhanced with elements made by the rapid neutron capture (“ r ”) process. As such, HD 222925 may be a new “template” for the observational r -process, where before the (much higher-metallicity) solar r -process residuals were used. In this work, we test under which conditions a single site accounts for the entire elemental r -process abundance pattern of HD 222925. We found that several of our tests—with the single exception of the black hole–neutron star merger case—challenge the single-site assumption by producing an ejecta distribution that is highly constrained, in disagreement with simulation predictions. However, we found that ejecta distributions that are more in line with simulations can be obtained under the condition that the nuclear data near the second r -process peak are changed. Therefore, for HD 222925 to be a canonical r -process template likely as a product of a single astrophysical source, the nuclear data need to be reevaluated. The new elemental abundance pattern of HD 222925—including the abundances obtained from space-based, ultraviolet (UV) data—call for a deeper understanding of both astrophysical r -process sites and nuclear data. Similar UV observations of additional r -process–enhanced stars will be required to determine whether the elemental abundance pattern of HD 222925 is indeed a canonical template (or an outlier) for the r -process at low metallicity.